The Role of Endoscopic and Surgical Treatment in Chronic Pancreatitis. (March 2020) - Udd, M.; Kylänpää, L.; Kokkola, A.
Chronic pancreatitis is a long-term illness leading to hospital admissions and readmission. This disease is often caused by heavy alcohol consumption and smoking. Patients with chronic pancreatitis suffer from acute or chronic pain episodes, recurrent pancreatitis, and complications, such as pseudocysts, biliary duct strictures, and pancreatic duct fistulas. Pancreatic duct strictures and stones may increase intraductal pressure and cause pain. Endoscopic therapy is aiming at decompressing the pressure and relieving the pain, most commonly with pancreatic duct stents and pancreatic duct stone retrieval. Early surgery is another option to treat the pain. In addition, endotherapy has been successful in treating complications related to chronic pancreatitis. The therapy should be individually chosen in a multidisciplinary meeting. Endoscopic therapy and surgery as treatment options for chronic pancreatitis are discussed in this review.